Ultraviolet-B-Induced Stomatal Closure in Arabidopsis Is Regulated by the UV RESISTANCE LOCUS8 Photoreceptor in a Nitric Oxide-Dependent Mechanism - Tossi, Vanesa Eleonora (2014)
UV RESISTANCE LOCUS8 (UVR8) signaling involves CONSTITUTIVELY PHOTOMORPHOGENIC1, the ELONGATEDHYPOCOTYL5 (HY5) transcription factor, and the closely related HY5 HOMOLOG. Some UV-B responses mediated byUVR8 are also regulated by nitric oxide (NO), a bioactive molecule that orchestrates a wide range of processes in plants. Inthis study, we investigated the participation of the UVR8 pathway and its interaction with NO in UV-B-induced stomatalmovements in Arabidopsis (Arabidopsis thaliana). Stomata in abaxial epidermal strips of Arabidopsis ecotype Landsbergerectaclosed in response to increasing UV-Bfluence rates, with maximal closure after 3-h exposure to 5.46mmol m–2s–1UV-B.Both hydrogen peroxide (H2O2) and NO increased in response to UV-B, and stomatal closure was maintained by NO up to24 h after the beginning of exposure. Stomata of plants expressing bacterial NO dioxygenase, which prevents NO accumulation, didnot close in response to UV-B, although H2O2still increased. When theuvr8-1null mutant was exposed to UV-B, stomata remainedopen, irrespective of thefluence rate. Neither NO nor H2O2increased in stomata of theuvr8-1mutant. However, the NO donorS-nitrosoglutathione induced closure ofuvr8-1stomata to the same extent as in the wild type. Experiments with mutants in UVR8signaling components implicated CONSTITUTIVELY PHOTOMORPHOGENIC1, HY5, and HY5 HOMOLOG in UV-B-inducedstomatal closure. This research provides evidence that the UVR8 pathway regulates stomatal closure by a mechanism involvingboth H2O2and NO generation in response to UV-B exposure.